Repetitive transcranial magnetic stimulation impacts the executive function of patients with vascular cognitive impairment: a systematic review and meta-analysis - Wang, Xu; Ding, Qixin; Li, Yuefang; Li, Tianshu; Li, Yakun; Yin, Jialin; Zhuang, Weisheng (Frontiers in Neurology, 2024)
Objective Executive dysfunction is a core symptom of vascular cognitive impairment (VCI), which seriously affects patients’ prognosis. This paper aims to investigate the effectiveness of rTMS on executive function in VCI. Methods The databases selected for this study included Pubmed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang, China Science and Technology Journal Database (VIP), and China Biology Medicine Disc (CBM). The screening times were conducted from the time of library construction until August 23, 2023. The inclusion criteria for this meta-analysis were randomized controlled trials (RCTs) on rTMS for VCI, which include executive function scores. The primary metrics were executive subscale scores of the Cognitive Comprehensive Scale and total scores of the Executive Specificity Scale. The secondary metrics were subscale scores of the Executive Specificity Scale. The quality of each eligible study was assessed using the Cochrane Risk of Bias tool. Meta-analysis and bias analysis were performed using Stata (version 16.0) and RevMan (version 5.3). Results A total of 20 high-quality clinical RCTs with 1,049 samples were included in this paper. The findings from the primary outcomes revealed that within the rTMS group, there were significantly higher scores observed for the executive sub-item on the cognitive composite scale (SMD = 0.93, 95% CI = 0.77–1.08, p < 0.00001, I2 = 14%) and the total score on the executive specific scale (SMD = 0.69, 95% CI = 0.44–0.94, p < 0.00001, I2 = 0%) compared to the control group. As for the secondary outcome measures, as shown by the Trail Making Test-A (time) (MD = −35.75, 95% CI = −68.37 to −3.12, p = 0.03, I2 = 55%), the Stroop-C card (time) (SMD = −0.46, 95% CI = −0.86 to −0.06, p = 0.02, I2 = 0%) and the Stroop-C card (correct number) (SMD = 0.49, 95% CI = 0.04–0.94, p = 0.03, I2 = 0%), the experimental group shorts time and enhances accuracy of executive task in comparison to the control group. Subgroup analysis of the main outcome demonstrated that intermittent theta burst stimulation (iTBS), higher frequency, lower intensity, longer duration, and combined comprehensive therapy exhibited superior efficacy. Conclusion rTMS is effective in the treatment of the executive function of VCI. The present study has some limitations, so multi-center, large-sample, objective indicators and parameters are needed to further explore in the future. Systematic review registration:https://www.crd.york.ac.uk/prospero/, CRD42023459669.